Green finance under the microscope: analysing South Africa's climate finance tracking capabilities at the sub-national level - Parker, Rabia (School of Economics, 2025)
The increasing global commitment to climate finance, particularly in the context of various international agreements, underscores the growing importance of greater transparency in tracking its allocation and impact. However, challenges persist in accurately assessing the allocation and impact of climate finance, particularly at the local and provincial (“Subnational”) levels in South Africa. Tools such as climate budget tagging have been developed to measure and mainstream the tracking of climate related expenditure into government systems and processes. However, challenges persist in accurately assessing the allocation and impact of climate finance, particularly at the local and provincial (“Subnational”). This thesis explores the feasibility of implementing Climate Budget Tagging (CBT) to track climate finance in South Africa's local government structures. The country's subnational governments have a particularly important role to play in tracking climate finance due to the ability they have to direct strategy, enhance transparency and boost accountability to their constituents. However, implementing this tool at the subnational level is not straightforward, due to systemic challenges that exist such as municipal governance, climate awareness and capacity constraints. Climate budget tagging is a relatively new concept in literature, with very little information on the impact of its implementation globally and in South Africa. Even though standardised structures have been created by major development partners such as the World Bank and UNDP, the idea is still being tested in several countries with different political and financial structures. Through a pragmatic research approach, combining desk reviews, interviews, and empirical data from the South African CBT pilot project led by OneWorld Sustainable Investments and Mokoro Consulting, this study identifies the pathways and challenges for successfully integrating CBT in local government systems. The research provides an analysis of South Africa's policy landscape and the institutional structures influencing climate finance, alongside international experiences with CBT. Using mixed methods, including data from the South African CBT pilot project, this study uncovers key challenges, such as capacity deficits, siloed governance, and resource constraints. It further identifies opportunities for integrating CBT into municipal systems, with a focus on strengthening accountability, building local expertise, and leveraging existing structures like the District Development Model. The findings emphasise the importance of long-term commitment, investment in education, and coordination across all government levels to ensure sustainable CBT implementation. The insights outlined by this research have key implications for policymakers and practitioners involved in climate finance and budgeting, offering practical guidance for integrating climate considerations into government budgets and enhancing transparency around the management of climate finance at the local level. This study contributes to a growing body of knowledge on tracking climate finance and offers practical guidance to developing CBT models in other regions.